An Improved Method for Extracting, Sorting, and AMS Dating of Pollen Concentrates From Lake Sediment - Tunno, Irene; Zimmerman, Susan R. H.; Brown, Thomas A.; Hassel, Christiane A. (Frontiers in Ecology and Evolution, 2021)
High-resolution chronologies are crucial for paleoenvironmental reconstructions, and are particularly challenging for lacustrine records of terrestrial paleoclimate. Accelerator Mass Spectrometry (AMS) radiocarbon measurement of terrestrial macrofossils is the most common technique for building age-models for lake sediment cores, but relies on the presence of terrestrial macrofossils in sediments. In the absence of sufficient macrofossils, pollen concentrates represent a valuable source of dates for building high-resolution chronologies. However, pollen isolation and dating may present several challenges, as has been reported by different authors in previous work over the last few decades. Here we present an improved method for extracting, purifying and radiocarbon-dating pollen concentrates using flow cytometry to improve the extraction efficiency and the purity of the pollen concentrates. Overall, the nature of the sediments and the abundance of the pollen represent a major consideration in obtaining enough pollen grains and, consequently, enough carbon to be dated. Further, the complete separation of pollen from other forms of organic matter is required to ensure the accuracy of the dates. We apply the method to surface samples and sediment cores recovered from two contrasting lake basins on the eastern side of the Sierra Nevada (California), and describe the variations that may be used to optimize pollen preparation from a variety of sediments.